Awards as Incentives - Susanne Neckermann; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2008)
Non-monetary incentives in the form of awards have so far escaped the attention of economists despite their widespread use. This paper presents an experiment conducted online at IBM to assess the impact of these kinds of extrinsic incentives. Introducing a hypothetical award has statistically significant effects on stated contributions to a public good. Our design allows the estimation of the impact of different award characteristics related to, for example, how public or how valuable the award is. We illustrate these findings by providing predictions about the behavior induced by a new award at IBM.
Keywords: C99; J33; M52; 330; incentives; non-monetary compensation; awards; motivation; experiment